2017
DOI: 10.1515/opag-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Maize and Potato Intercropping: A Technology to Increase Productivity and Profitability in Tigray

Abstract: Smallholders have limited landholding in the highlands of Tigray and therefore there is a critical need to improve land use efficiency (LUE). One way to improve the LUE is through intercropping of companion crops including maize and potato. An experiment was conducted to evaluate the intercropping ratio as a means to improve land use efficiency during the 2012 cropping season. The treatments tested were three intercropping ratios of maize: potato in 1:1, 1:2, 2:1 row arrangement compared against the maize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…First, farmers believe that adoption of climate smart innovations enhances food security through increasing productivity and income (91 and 80%, respectively), which is also supported by other studies in sub-Saharan Africa and Ethiopia. For instance, farmers who adopt maize potato intercropping, intercropped maize with grain legumes increased crop productivity (Baudron et al , 2014; Kidane et al , 2017; Miheretu, 2014; Thierfelder et al , 2012; Valbuena et al , 2012) and (Lal, 2006; Lorenz and Lal, 2014) argued that agroforestry increases yield via increased soil organic carbon. Other studies also support result and reported that crop residue retention and crop rotation and/or intercrop association among other benefits increase yield (Ngwira et al , 2013).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, farmers believe that adoption of climate smart innovations enhances food security through increasing productivity and income (91 and 80%, respectively), which is also supported by other studies in sub-Saharan Africa and Ethiopia. For instance, farmers who adopt maize potato intercropping, intercropped maize with grain legumes increased crop productivity (Baudron et al , 2014; Kidane et al , 2017; Miheretu, 2014; Thierfelder et al , 2012; Valbuena et al , 2012) and (Lal, 2006; Lorenz and Lal, 2014) argued that agroforestry increases yield via increased soil organic carbon. Other studies also support result and reported that crop residue retention and crop rotation and/or intercrop association among other benefits increase yield (Ngwira et al , 2013).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Although there is overlap in CSA pillar perceptions, the independent variables were crafted from the three pillars of CSA based on reviewed literature. Hence, the inclusion of independent variables in the model specification is also based on past empirical literature on the determinants of adoption of agricultural technologies (Alomia-Hinojosa et al , 2018; Baudron et al , 2015; Giller et al , 2009; Kassie et al , 2015; Kidane et al , 2017; Kumar et al , 2015; Miheretu, 2014; Teklewold et al , 2017, 2019; Thierfelder et al , 2012). The independent variables selected for this study include perceptions: CSA increases productivity, soil fertility, income, soil organic matter, diversifies livestock feed sources and diversifies alternative energy sources; CSA reduces the cost of production, the amount of synthetic fertilizer used, soil erosion, seeding rate, weed infestation and crop failure; and CSA rehabilitates land.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies conducted in Ethiopia, pointed out that intercropping of maize with different crops including soybean and desmodium resulted in reduced termite damage to maize and increased maize yield for the improved farmers' livelihoods [20]. Related studies conducted in Tigray, Ethiopia pointed out that In this study, one maize and two potato row arrangement showed 58% yield advantage over the sole cropping thus improving household food security and income [21]. The finding of this study also agree with the study conducted in Alvorada do Gurguéia which concluded that intercropping maize with cover crops increased maize grain yield, macronutrient contents, and straw dry matter accumulation and grain yield of cowpeas [22].…”
Section: Discussionmentioning
confidence: 54%
“…Maize intercropping with faba bean was recommended at Adet as profitable cropping system (Tilahun et al, 2012). Intercropping potato with maize was recommended for central highlands of Ethiopia such as Holeta (Temesgen and Wondimu, 2012) in Tigray region (Beyenesh et al, 2017) in Wollo (Bantie, 2015). Rotation of maize with pulses (haricot bean, soyabean, pigeonpea), oil crops (noug), was also recommended as a best practice in Bako and similar area (Tesfa et al, 2001).…”
Section: Maize Cropping Systemmentioning
confidence: 99%